A HYBRID FIXED POINT THEOREM WITH PPF DEPENDENCE IN BANACH ALGEBRAS AND APPLICATIONS TO QUADRATIC FUNCTIONAL DIFFERENTIAL EQUATIONS. (2015) - DHAGE, BAPURAO C.; JADHAV, NAMDEV S.; SHETE, ANURUDRA Y.
No abstract available